Android-Based Sign Language Learning and Evaluation Apps - Husain T; Nurdiansah Nurdiansah; Cucut Susanto; Uzaimin Nasruddin; Muh. Farhan Hidayat (Universitas Raharja, 2022)
Sign language is a language that prioritizes body language and lip movements, not sound, in communicating. The deaf and speech impaired are the main group who use this language by combining the form of finger movement, orientation and movement of the hands, arms, and body, to express their thoughts. This application uses pictures and questions to find out the information they convey. So this application was designed so that it can help the general public to receive information from the deaf and speech impaired by using Black Box testing to test for functional errors contained in the application.